2008
DOI: 10.1111/j.1365-2966.2008.13351.x
|View full text |Cite
|
Sign up to set email alerts
|

Dwarf spheroidals in MOND

Abstract: We take the line‐of‐sight velocity dispersions as functions of radius for eight Milky Way dwarf spheroidal galaxies and use Jeans analysis to calculate the mass‐to‐light ratios (M/L) in Modified Newtonian Dynamics (MOND). Using the latest structural parameters, distances and variable velocity anisotropy, we find six out of eight dwarfs have sensible M/L using only the stellar populations. Sextans and Draco, however, have M/L = 9.2+5.3−3.0 and 43.9+29.0−19.3 respectively, which poses a problem. Apart from the n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
144
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(155 citation statements)
references
References 80 publications
7
144
2
Order By: Relevance
“…µ=0,α=0 (Newtonian) µ=0.01,α=10 µ=0.01,α=100 µ=10,α=10 µ=10,α=100 µ=100,α=10 µ=100,α=100 external field effect (EFE) must be taken into account when dealing with objects embedded in the external tidal field of a more massive system (Angus 2008;Haghi et al 2009;Malekjani, Rahvar & Haghi 2009;Haghi, Baumgardt & Kroupa 2011;Haghi et al 2016). This is because of the intrinsic non-linearity of the Poisson equation that is related to the violation of the strong equivalence principle in MOND.…”
Section: R [Pc]mentioning
confidence: 99%
See 1 more Smart Citation
“…µ=0,α=0 (Newtonian) µ=0.01,α=10 µ=0.01,α=100 µ=10,α=10 µ=10,α=100 µ=100,α=10 µ=100,α=100 external field effect (EFE) must be taken into account when dealing with objects embedded in the external tidal field of a more massive system (Angus 2008;Haghi et al 2009;Malekjani, Rahvar & Haghi 2009;Haghi, Baumgardt & Kroupa 2011;Haghi et al 2016). This is because of the intrinsic non-linearity of the Poisson equation that is related to the violation of the strong equivalence principle in MOND.…”
Section: R [Pc]mentioning
confidence: 99%
“…Using Jeans analysis in MOND, Angus (2008) showed that the stellar M/L ratio of four out of eight dSphs with the highest surface brightness (highest internal gravities) are compatible with the stellar population synthesis (SPS) models with reasonable M/L ratios, but the other four required M/L ratios that were larger than the expected range of 1 -5 in the V -band found from stellar population modelling (Maraston 2005). He argued that the latter four dSphs may be subject to tidal forces that produce tidally unbound interloper stars and inflate the velocities of the bound stars.…”
Section: Introductionmentioning
confidence: 99%
“…Kroupa 1997), the presence of a large amount of non-baryonic dark matter (e.g Wolf et al 2010;Tollerud et al 2012), or as a modification of the Newtonian law of gravity at very low accelerations (e.g. Angus 2008;McGaugh & Milgrom 2013).…”
Section: Detailed Description Of the Datamentioning
confidence: 99%
“…Lokas 2002) or MOND frameworks (e.g. Angus 2008) and could be included in subsequent analysis. We point to the recent work by Gilmore (2007), in which isothermal conditions are used to model local dSph galaxies assuming Newtonian gravity.…”
Section: Local Dwarf Spheroidal Galaxiesmentioning
confidence: 99%
“…Still, this last point remains somewhat controversial. Angus (2008) suggests that the MOND proposal will hold for local dSph galaxies, once the effects of tidal disruption are adequately incorporated.…”
Section: Introductionmentioning
confidence: 99%